Large-scale cellulose-assisted transfer of graphene toward industrial applications. (December 2016) - Chen, Mingguang; Li, Guanghui; Li, Wangxiang; Stekovic, Dejan; Arkook, Bassim; Itkis, Mikhail E.; Pekker, Aron; Bekyarova, Elena; Haddon, Robert C.
Abstract: CVD graphene has attracted a great deal of interest from both academia and industry. The strong motivation to commercialize high quality CVD graphene films and related devices has been restricted by the lack of a cheap, efficient, clean and reliable graphene transfer process. In this article, we report a novel graphene transfer technique which provides a route to high-throughput, reliable and economical transfer of graphene without introducing large cracks and residue contamination from polymers, such as PMMA or magnetic impurities. The transferred graphene was thoroughly characterized with Raman spectroscopy, Atomic Force Microscopy, and X-ray photoelectron spectroscopy. Fabricated large area graphene-based field effect transistors exhibited high mobilities, which were about 2 times higher than those for devices prepared with graphene transferred by the conventional wet transfer method. This new graphene transfer technique has the potential to expedite the large scale industrial utilization of CVD graphene in electronics, spintronics, catalysis and energy storage.